UTILIZATION OF BUSINESS INTELLIGENCE IN BUSINESS DECISION MAKING - Sudiantini, Dian; Fadhilah, Ernita Shafa Nur; Wijayanti, Maylinda; Pratiwi, Rahmaliya; Hanifah, Rizka Nurul (LPPM Institut Pendidikan Nusantara Global, 2024)
Making wise and well-informed company decisions at a time where data is the most valuable resource requires the application of business intelligence (BI). Big Data is handled by modern BI, which also benefits from more processing power, fast data access, opportunity detection, and risk mitigation. In order to correctly represent the facts, this research employs a qualitative technique and gathers data from several sources. The study's findings demonstrate the importance of business intelligence in corporate decision-making. In order to assist educated decision-making, plan development plans, and offer insight into internal and external performance, business intelligence (BI) gathers data from a variety of sources. Implementing BI necessitates a business and technological expertise, but it also makes difficult data analysis easier, boosts productivity, and helps identify possibilities and resolve issues. Business Intelligence (BI) is critical to success in the current day because it gives reliable information, increases operational efficiency, and assists management in making decisions that are responsive to changes in the market. The study's findings also demonstrate how BI gathers information from a variety of sources to offer perception into the market, consumer behavior, and internal business performance.